Bamboo (Acidosasa edulis) shoot shell biochar: Its potential isolation and mechanism to perrhenate as a chemical surrogate for pertechnetate. (December 2016) - Hu, Hui; Jiang, Bangqiang; Wu, Huixiong; Zhang, Jubin; Chen, Xiaohui
Abstract: In this work, a biochar was prepared from bamboo ( Acidosasa edulis ) shoot shell through slow pyrolysis (under 300–700 °C). Characterization with various tools showed that the biochar surface was highly hydrophobic and also had more basic functional groups. Batch sorption experiments showed that the biochar had strong sorption ability to perrhenate (a chemical surrogate for pertechnetate) with maximum sorption capacity of 46.46 mg/g, which was significantly higher than commercial coconut shell activated carbon and some adsorbents reported previously. Desorption experiments showed that more than 94% of total perrhenate adsorbed could be recovered using 0.1 mol/L KOH as a desorption medium. Pearson correlation analysis showed that the recovery of perrhenate by the biochars was mainly through surface adsorption mechanisms involving both high hydrophobicity and high basic sites of biochar surface. Graphical abstract: Highlights: Rhenium can be as a reliable surrogate for radioactive technetium. AESS biochar has strong adsorption ability to perrhenate in acidic solution. Maximum adsorption capacity was 46.46 mg/g. High hydrophobicity and basic site of biochar contribute to recovering perrhenate.